The clinical and genetic features in patients coexisting primary breast and thyroid cancers - Jingyao Fu; Jingyao Fu; Miao He; Qiong Wu; Xiangkai Zhang; Xiangkai Zhang; Xin Qi; Keyu Shen; Xiaochun Wang; Guang Zhang (Frontiers in Endocrinology, 2023)
BackgroundWe attempted to examine the clinical characteristics in patients with breast cancer (BC) and thyroid cancer (TC); explore the potential mechanisms of tumorigenesis and progression.MethodsUsing the Surveillance, Epidemiology, and End Result Program-9 (SEER-9) database, a retrospective study (1975-2017) was conducted on patients with BC and TC. We identified the common differentially expressed genes involved in BC and TC using the Gene Expression Omnibus database (GEO). Immunohistochemical staining (IHC) was performed to verify the expression of the hit gene in patients with co-occurrence of BC and TC. Using The Cancer Genome Atlas (TCGA) database, the relationship between gene expression and clinicopathological characters was determined. Gene set enrichment analysis (GSEA) was used to identify the pathways enriched in BC and TC.ResultsBC patients had a higher predisposition to develop TC (standardized incidence ratio, SIR: 1.29) and vice-versa (SIR: 1.12). Most of these patients were differentiated thyroid carcinoma (DTC) and hormone receptor (HR) - positive BC. The mRNA expression of COMP (Cartilage oligomeric matrix protein) was significantly overexpressed in BC and TC by analyzing the GEO database. The protein expression of COMP was increased in both BC and TC tissues obtained from the same patients validated by IHC. COMP was correlated with worse OS in BC (stage II-IV) and TC; it was the independent factor for prognosis of BC. GSEA indicated that the estrogen response and epithelial-mesenchymal transition (EMT) pathways were significantly enriched in both TC- and BC- COMP overexpressed groups.ConclusionThe co-occurrence risk of BC and TC in the same individual is higher than in the general population. Overexpression of COMP could promote oncogenesis and progression in patients with BC and TC through estrogen signaling and EMT pathways.